Keilschrifttexte verschiedenen Inhalts - Borger, R. (Fs Böhl)
der astrologische Text CB (photo); 4R1 24 No. 1 (=K. 4809) + K. 4925, Dupl. KUB 4 No. 7; Baurituale Si. 12, Si. 36, PBS 1/2 124, K. 3664 +.